The naval revolts in Callao: 1932 and 1948 - Ortiz Sotelo, Jorge (1999)
Civil-military relations are always a difficult issue to handle, and in the case of Peru they reached a particularly critic moment in the present century, in 1932 and 1948, when some naval personal, linked to the Aprista Party, raised in arms aiming to impose its party ideals. Both revolts were quickly and violently reduced, with some bloodshed in both sides. Afterwards, the rebels were prosecuted by the Naval Justice and eight of those involved in the 1932 revolt where found guilty and executed.   The present article aims to compare similarities and differences between both revolts, pointing out the lessons taken both by the Peruvian Navy as well as the Aprista Party.